Brand perception towards Perodua car: Myvi / Salinah Morni - Morni, Salinah (2005)
A survey was carried out in September 2005 to evaluate the customers perception toward the Perodua product and services. The main reason behind the research is to find out what are the factors that contribute to customers perception and preferences towards a car. This research will only focus on Perodua services and the features of Myvi car launched by Perodua recently. Does Perodua services contribute to customers preferences towards its product? Does safety features add to customers preferences towards Myvi car? This research use convenience sampling method and quota sampling method in order to get a fair representative ofrespondents in Kuching . This paper comprises of five main chapters. The First Chapter is the introduction and it covers the background of study, scope of study, problem statement, objectives, significance, research questions and limitation of study. The Second Chapter covers the literature review ofthe study. Chapter Three detailed on research methodology. Chapter Four is the data analysis and finding. Finally Chapter Five consist of conclusion and recommendation to the problem ofthe study. With the finding of the study , it is hope that it will become a reference or act as a guidelines for students and valuable guidelines for Perodua management in developing marketing strategies to reach target market.